PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MERANCANG FITUR APLIKASI PENJUALAN BUKU ONLINE - Utami, Ema; -, Sarkawi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Due to high competition in the business world especially at the bookstore having critical thinking skills to breakthrough the sales performance. Customer Relationship Management (CRM) is an approach used to know, identify and recognize the customer expectation to the company. Today's information system era made customer easier to purchase books using online system. Online bookstore having comprehensive information, many services is what customer looking for.The purpose of designing applications online book sales by implementing CRM is to help increase book sales, improve customer satisfaction, increase customer loyalty, providing convenience to customers to obtain information about book price and availability, provide service complaints, comments and suggestions, and provide services ease of ordering books.